A paradigm shift in the construction industry - Heidenwolf, Orsolya; Szabó, Roland Zsolt (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2024)
The international construction market is rapidly adopting digitalisation and innovation to tackle climate change and sustainability challenges. 32 industry professionals with international experience were surveyed with interviews to gather their views on the digital transformation of the construction industry. The research findings suggest that achieving the Construction 4.0 paradigm shift requires more than just technological innovation. Interdisciplinary collaboration and system integration are also necessary for this complex transformation. Based on the findings, the Hungarian construction industry must prioritise the integration of data management and information systems, and enhance data-driven collaboration between market players and professionals.